Pemanfaatan Limbah Ampas Tahu Menjadi Kompos pada Industri Tahu di Desa Ploso Kecamatan Jati Kabupaten Kudus - Endang Dewi Murrinie; Hendy Hendro Hadi Sridjono; Nindya Arini (Universitas Muria Kudus, 2022)
Ploso Village, Jati District, Kudus is one of the tofu production centers in Kudus, there are about 30 tofu industries. The existence of a tofu factory will cause waste problems, both liquid waste, and solid waste. The percentage of solid waste in the form of tofu dregs is around 70% and is currently not widely used. This solid waste will cause environmental pollution if it is not used immediately. Tofu waste contains nitrogen, phosphorus, potassium, magnesium, calcium, iron, and organic carbon (C) which can be used as compost to increase soil and plant fertility. Community service activities with the title